THU0104 Both MRI and HAQ-DI can predict relapses following all treatment withdrawal in MTX-NAÏVE patients with RA in remission after 12 months of abatacept therapy in the avert trial. (15th June 2017) - Ahmad, H; Baker, J; Østergaard, M; Emery, P; Huizinga, T; Ye, J; Banerjee, S; Conaghan, P
Abstract : Background: Factors predictive of relapse need to be identified to aid therapy withdrawal decisions for patients with RA achieving remission with treatment. AVERT (NCT01142726 ) was a Phase IIIb, randomized, active-controlled trial in patients with early RA. 1 After a 12-month, double-blind treatment period with abatacept + MTX, or abatacept or MTX monotherapy, patients with DAS28 [CRP] <3.2 could enter a 12-month withdrawal period (all treatment stopped). Objectives: To evaluate post hoc whether MRI scores, patient characteristics and disease activity at Month 12 were predictors of clinical relapse at Month 18 and Month 24 after treatment withdrawal in AVERT. Methods: Synovitis, erosion and bone oedema in the dominant hand and wrist MRI were scored at Month 12 using the RA MRI scoring system (RAMRIS). Patient characteristics (pain, age, weight, HAQ-DI) and disease measures (CRP, SJC28, TJC28, DAS28 [CRP], CDAI, SDAI) were recorded at Month 12. The influence of these factors on the proportion of patients who relapsed (doubling of TJC28 and SJC28, and DAS28 [CRP] ≥1.2 increase relative to Month 12) by Month 18 and Month 24 was assessed. Results: A total of 172 patients achieving DAS28 remission (DAS28 [CRP] <2.6) at Month 12 in any treatment group were included in the analysis. Numbers of patients who relapsed at Month 18 and Month 24 were 100 and 113, respectively. Of the patient characteristics, disease activity and imaging factors analysed at Month 12, only MRI synovitis, erosion and oedema scores, as well as HAQ-DI scores, were significantly associated (p<0.05) with relapse status at both Month 18 and Month 24 (Table). Conclusions: MRI and HAQ-DI scores in patients in DAS28 remission predicted clinical relapses 6 and 12 months after complete drug withdrawal in the AVERT trial. The clinical decision on whether to withdraw therapy in MTX-naïve patients with RA in remission may benefit from an assessment of imaging and physical function prior to drug withdrawal. References: Emery P, et al. Ann Rheum Dis 2015;74:19–26. Disclosure of Interest: H. Ahmad Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Baker: None declared, M. Østergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Janssen, Merck, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Centocor, GSK, Hospira, Janssen, Merck, Mundipharma, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Schering-Plough, Roche, Takeda, UCB, Wyeth, P. Emery Grant/research support from: AbbVie, Merck, Pfizer, Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, Lilly, Novartis, Samsung Bioepis, T. Huizinga Grant/research support from: EU & Dutch Arthritis Foundation, Consultant for: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Crescendo Biosciences, Inc, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, UCB, Inc., Eli Lilly, Speakers bureau: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, P. Conaghan Grant/research support from: Bristol-Myers Squibb, Consultant for: AbbVie, Lilly, Novartis, Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Roche